Emerging roles for Rho GTPases operating at the Golgi complex. (2nd November 2021) - Mysior, Margaritha M.; Simpson, Jeremy C.
ABSTRACT: Rho GTPases are known to play an essential role in fundamental processes such as defining cell shape, polarity and migration. As such, the majority of Rho GTPases localize and function at, or close to, the plasma membrane. However, it is becoming increasingly clear that a number of Rho family proteins are also associated with the Golgi complex, where they not only regulate events at this organelle but also more widely across the cell. Given the central location of this organelle, and the numerous membrane trafficking pathways that connect it to both the endocytic and secretory systems of cells, it is clear that the Golgi is fundamental for maintaining cellular homoeostasis. In this review, we describe these GTPases in the context of how they regulate Golgi architecture, membrane trafficking into and away from this organelle, and cell polarity and migration. We summarize the key findings that show the growing importance of the pool of Rho GTPases associated with Golgi function, namely Cdc42, RhoA, RhoD, RhoBTB1 and RhoBTB3, and we discuss how they act in concert with other key families of molecules associated with the Golgi, including Rab GTPases and matrix proteins.